A Detailed Thermal Model of a Parabolic Trough Collector Receiver - Kalogirou, Soteris A. (My University, 2012)
Parabolic trough collectors are made by bending a sheet of reflective material into a parabolic shape. A metal black pipe, covered with a glass tube to reduce heat losses, is placed along the focal line of the collector. The concentrated radiation reaching the receiver tube heats the fluid that circulates through it, thus transforming the solar radiation into useful heat. It is sufficient to use a single axis tracking of the sun and thus long collector modules are produced. In this paper a detailed thermal model of a parabolic trough collector is presented. The thermal analysis of the collector receiver takes into consideration all modes of heat transfer; convection into the receiver pipe, in the annulus between the receiver and the glass cover, and from the glass cover to ambient air; conduction through the metal receiver pipe and glass cover walls; and radiation from the metal receiver pipe and glass cover surfaces to the glass cover and the sky respectively. The model is written in the Engineering Equation Solver (EES) and is validated with known performance of existing collectors and subsequently is used to perform an analysis of the collector we are going to install at Archimedes Solar Energy Laboratory at the Cyprus University of Technology.
Keywords: Parabolic trough; Heat loss; Conduction; Convection radiation; Receiver thermal performance